The influence of exothermic reactions on the nonequilibrium level of discharge plasma - Chernyak, V.Ya.; Iukhymenko, V.V.; Prysiazhnevych, I.V.; Martysh, Eu.V. (Вопросы атомной науки и техники, 2013)
The comparative analysis of plasma parameters of transverse arc and discharge in the gas channel with liquid wall was made for different working gas and liquids (for air, distilled water and for its mixtures with ethanol). Electronic excitation temperatures Te* of atoms, vibrational Tv* and rotational Tr* temperatures of molecules in the generated plasma were determined by optical emission spectroscopy. It was shown that both discharges generate nonequilibrium plasma in the case of working gas air and working liquid – distilled water. Adding a fuel (ethanol) into the plasma system with O2 leads to the increasing of rotational and vibrational temperatures of molecules, which became equal to each other within the errors. This may indicate that the exothermic reactions reduce the level of nonthermality of the generated plasma as a result of additional energy supply for heavy components in the process of complete combustion of hydrocarbons.